UTILIZATION OF LEARNING MEDIA MY MAP MY ADVENTURE TO INCREASE GEOGRAPHY LEARNING RESULTS - dony purnomo (GeoEco, 2018)
The aim of this reseach are: to (1) Describe the utilization of my map my adventure to improve learning outcomes on geography subject, (2) To know the improvement of learning outcomes through the application of learning media my map my adventure on geography subjects. This classroom action research uses two cycles in class XI IPS 4 SMAN 1 Purwantoro study year 2017/2018. The indicator of success in this study mastery of classical learners is above 65% and increase learning outcomes of learners. The results of this research are: (1) Utilization of my map my adventure media through several stages of archipelagic activities, core activities consisting of learners reading various references, forming groups, playing my map my adventure, presentation and ending with closing activities, (2) Utilization media my map my adventure can improve the learning result of geography. Increased learning outcomes are reflected in students who complete the pre cycle is 9 students (36%) of unfinished 16 students (64%), in the cycle I learners who complete as many as 15 students (60%) while the unfinished as many as 10 students (40%), in cycle II learners who completed up to 22 (88%) and unfinished to 3 students (12%).